Pengaruh Pendekatan Konflik Kognitif Terhadap Kemampuan Berpikir Kritis Pada Materi Gerak Lurus - Sutrio Sutrio; Muh. Makhrus; Armi Larasati (Kappa Journal, 2020)
This study aims to determine the effect of the cognitive conflict approach on the critical thinking skills of senior high school students in grade X on straight motion material. This type of research is a pre-experimental research design with One Group Pretest-Posttest Design. The population in this study were all students of class X MIPA SMAN 1 Narmada. The research sample was obtained using a purposive sampling technique, obtained class X MIPA 1 as experimental class 1, class X MIPA 2 as experimental class 2, and class X MIPA 3 as experimental class 3. Data collection on critical thinking skills used essay test as many as 5 questions. Hypothesis test analysis used a statistical paired sample t-test and showed that Ho was rejected and Ha was accepted. This shows that the cognitive conflict approach affects the critical thinking skills of students in straight motion material.